Adaptive Dead Zone Compensation Control Method for Electro-Hydrostatic Actuators Under Low-Speed Conditions - Haoyi Jiang; Zhenfei Ling; Fengqi Zhou; Maowen Sun; Hao Liu; Lilin Xu; Yeming Yao; Xiaoping Ouyang; Huayong Yang (Chinese Journal of Mechanical Engineering)
Abstract This study proposes an accurate dead zone compensation control method for electro-hydrostatic actuators (EHAs) under low-speed conditions. Specifically, the nonlinear dead zone characteristics under low-speed conditions are summarized based on numerous EHA experiments. An adaptive compensation function (ACF) is then constructed for the dead zone. Next, this study proposes an adaptive dead zone compensation control method for EHAs by integrating the ACF with a virtual decomposition controller (VDC) based on the established EHA model. The stability of the proposed control method is also proven. Finally, the proposed control method is verified using an EHA platform. The test results show that the dead zone trajectory tracking errors of EHAs are significantly reduced when combined with the ACF. Furthermore, since most EHAs are controlled by adjusting the motor speed, the method presented in this study is simpler and easier to use than methods that employ flow compensation.